2010
DOI: 10.1111/j.1369-7625.2010.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of carrying their own health information: approaches towards responsibility and playing an active role in their own health – implications for a patient‐held health file

Abstract: Objective To elicit patientsÕ views on whether they could contribute to improvements in their care by carrying their own health information to clinician encounters; and to consider the implications for the development of a patient-held health file (PHF).Background Increasing rates of chronic disease lead to health care being delivered by multiple care providers often at distributed geographic locations. As a way of increasing the availability of patient information to care providers our project will trial a PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Of the remaining 24 studies, 14 were excluded for the following reasons: (i) involved solely interviews with staff ( n = 2); (ii) involved questionnaire surveys only ( n = 5); (iii) were systematic reviews ( n = 3); (iv) were non‐empirical service evaluations ( n = 2); and (v) case report ( n = 1) or (vi) considered the views of bereaved relatives and carers only ( n = 1). Ten papers that reported the experiences of 455 patients were included in the thematic synthesis …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 24 studies, 14 were excluded for the following reasons: (i) involved solely interviews with staff ( n = 2); (ii) involved questionnaire surveys only ( n = 5); (iii) were systematic reviews ( n = 3); (iv) were non‐empirical service evaluations ( n = 2); and (v) case report ( n = 1) or (vi) considered the views of bereaved relatives and carers only ( n = 1). Ten papers that reported the experiences of 455 patients were included in the thematic synthesis …”
Section: Resultsmentioning
confidence: 99%
“…In nine studies, the experience and training of the research team was neither reported nor discernible. In only one study, a qualitative sampling strategy (theoretical sampling) had been explicitly reported. In eight studies, major themes were clearly represented in the findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, research from the patient perspective has highlighted the value of patients understanding of information for them to participate in their care and to make informed decisions (Davis et al., ; Eldh, Ehnfors, & Ekman, ; Longtin et al., ). Patients who have been comprehensively informed are also more likely to feel confident and trust their own decisions (Forsyth, Maddock, Iedema, & Lessere, ; Longtin et al., ). Provision of appropriate and sufficient information in a supportive environment are key points in patient involvement (Larsson, Sahlsten, Sjostrom, Lindencrona, & Plos, ).…”
Section: Discussionmentioning
confidence: 99%
“…Provision of appropriate and sufficient information in a supportive environment are key points in patient involvement (Larsson, Sahlsten, Sjostrom, Lindencrona, & Plos, 2007). Patients who have access to information on their health and care are more willing and able to be involved in safety issues (Forsyth et al, 2010;Iedema et al, 2012). It is likely that patients who receive adequate information become more knowledgeable about what to expect from nursing activities, treatment and care, which enables them to detect potential deviations of relevance for patient safety.…”
Section: Discussionmentioning
confidence: 99%